2016
DOI: 10.3390/su8060582
|View full text |Cite
|
Sign up to set email alerts
|

Coordinated Development Analysis of the “Resources-Environment-Ecology-Economy-Society” Complex System in China

Abstract: Abstract:The aim of investigating the coordination of the complex system constituted by resources, environment, ecology, economy and society subsystems (CSR3ES), is to achieve sustainable development by: (1) describing the complicated relationships of the inner-subsystems and inter-systems; (2) designing the calculation method of the coordination degree for CSR3ES; (3) analyzing its developing trends from a macro point of view through comprehensive coordination degree; and (4) to determine the direction of sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…relationship between carbon dioxide emissions, energy consumption, population growth, and economic growth in Nigeria, and confirmed the validity of the environmental Kuznets curve hypothesis. Xie et al [58] quantitatively evaluated the level of coordinated development of resource, environment, ecology, economic, and social subsystems of China's 31 provinces in 2013, and obtained similar results with this paper. They found that the coordinated development provinces are mainly concentrated in the eastern coastal areas of China, while the central and western regions are lowcoordinated and uncoordinated development provinces.…”
Section: The Analysis Of the Coupling Coordinated Developmentsupporting
confidence: 79%
See 1 more Smart Citation
“…relationship between carbon dioxide emissions, energy consumption, population growth, and economic growth in Nigeria, and confirmed the validity of the environmental Kuznets curve hypothesis. Xie et al [58] quantitatively evaluated the level of coordinated development of resource, environment, ecology, economic, and social subsystems of China's 31 provinces in 2013, and obtained similar results with this paper. They found that the coordinated development provinces are mainly concentrated in the eastern coastal areas of China, while the central and western regions are lowcoordinated and uncoordinated development provinces.…”
Section: The Analysis Of the Coupling Coordinated Developmentsupporting
confidence: 79%
“…Furthermore, Aiyetan and Olomola [18] studied the relationship between carbon dioxide emissions, energy consumption, population growth, and economic growth in Nigeria, and confirmed the validity of the environmental Kuznets curve hypothesis. Xie et al [58] quantitatively All the provinces studied are classified according to the classification criteria of the coupling coordination degree (Figure 2). The following points can be made.…”
Section: The Analysis Of the Coupling Coordinated Developmentmentioning
confidence: 99%
“…Remanufacturing components are assumed to be as new. 4. Inventory holding, remanufacturing, purchasing, disposal, and backlogging costs are deterministic.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Moreover, the consolidation of regional industrial division of labor and development paths has intensified the imbalance of spatial development (Li & Wang, 2016). The purpose of coordinated regional development is to bring into play the comparative advantages and enthusiasm of different regions, and gradually reduce the gap in regional development through the improvement of market mechanisms, cooperation mechanisms, mutual assistance mechanisms, and support mechanisms to form a new pattern of complementary advantages and coordinated development among different regions (Xie et al, 2016). From the beginning of the Ninth Five-Year Plan, China has implemented a series of major strategies to promote coordinated regional development, including the rise of the central region and the development of the western region.…”
Section: Introductionmentioning
confidence: 99%